Ipar adalah Maut: Analisis Semiotika Representasi Pengkhianatan dan Keretakan Rumah Tangga - Bunga Rahma Sindisa (Universitas Merdeka Malang, 2026)
Film is a reflection of social reality capable of constructing complex phenomena such as infidelity into a system of signs. This study aims to uncover the representation of betrayal and household breakdown in the film